1973
DOI: 10.1111/j.1432-1033.1973.tb03123.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Specificity of Interactions between Transfer Ribonucleic Acids and Aminoacyl‐tRNA Synthetases

Abstract: The interactions of yeast seryl-tRNA and phenylalanyl-tRNA synthetases with the cognate and the noncognate tRNA have been studied by fluorescence spectroscopy. The binding process was followed by observing the changes in tryptophan fluorescence of the synthetases as well as the changes in the polarized fluorescence of the tRNAs covalently labeled with ethidium bromide, proflavine, or l,N6-etheno-ATP. The degree of polarization of the fluorescence labels is particularly sensitive to changes in rotational diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…In fluorescence studies [5], cooperativity has been previously indicated for the binding of tRNAser to seryl-tRNA synthetase. I n studies of protection against nuclease digestion [S] and in fluorescence measurements [5,7,39] two sites for tRNAser were obtained. Unfortunately attempts to determine serine binding sites by equilibrium dialysis were unsuccessful, due to the low binding constant (which correlates with the relatively high "Rm").…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fluorescence studies [5], cooperativity has been previously indicated for the binding of tRNAser to seryl-tRNA synthetase. I n studies of protection against nuclease digestion [S] and in fluorescence measurements [5,7,39] two sites for tRNAser were obtained. Unfortunately attempts to determine serine binding sites by equilibrium dialysis were unsuccessful, due to the low binding constant (which correlates with the relatively high "Rm").…”
Section: Discussionmentioning
confidence: 99%
“…This additional protection disappeared when the tRNA was aminoacylated, while in the absence of Phe-ol-pA no difference in protection was detected between charged and uncharged tRNA. In initial fluorescence polarization studies no change in binding of modified tRNAs to the cognate synthetase was observed, when up to I mM Phe-ol-pA or Ser-ol-pA was added [7], although the degree of polarization was influenced by ATP.…”
Section: Experiments With Arninmll$ Adenyhtatesmentioning
confidence: 92%
See 2 more Smart Citations
“…The derivatives of yeast tRNAPhe have been shown to be active in a number of assays including the ribosome systems from E. coli [13] and reticulocytes [14], indicating that their structure is not very different from that of native tRNAPhe. Both proflavine-labeled and ethidium-labeled tRNAPh" have been successfully used in a fluorescence spectroscopic study of synthetase-tRNA interaction [15]. For the present study of tRNA-ribosome interaction, we have used the ethidium label because it has a rather long fluorescence life time, making it suitable for polarization measuremets, and because its fluorescence properties are sensitive to conformational changes of the nucleic acid [16] (and M. Ehrenberg, R. Rigler, and W. Wintermeyer, unpublished results).…”
mentioning
confidence: 99%